2007
DOI: 10.1002/mds.21188
|View full text |Cite
|
Sign up to set email alerts
|

Valproate‐induced Parkinsonism in epilepsy patients

Abstract: We systematically examined 226 epilepsy patients in a tertiary-referral center and found 6 (5.04%) to have valproate-induced Parkinsonism. There was a significantly higher prevalence of patients with Parkinsonism in the group of patients treated with valproate compared to those who were on other antiepileptic drugs (6 [5.04%] of 119 vs. 0 [0%] of 107; chi2 = 5.54; P = 0.025). These six patients had been on valproate for more than 3 years (mean, 75.67 +/- 25.32 months) at an average dose of 750 +/- 273.86 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 11 publications
0
35
0
1
Order By: Relevance
“…Although the mechanism of SV-induced parkinsonism is not known, several biological theories have been proposed to explain this increased risk, including an effect on complex I activity in the electron transport chain of mitochondria [25] and on GABAergic pathways in the basal ganglia [32]. Apart from that, both oxidative stress and mitochondrial dysfunction have are also been attributed [27]. Functional neuroimaging in a few cases has shown that the striatonigral function appeared to be minimally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of SV-induced parkinsonism is not known, several biological theories have been proposed to explain this increased risk, including an effect on complex I activity in the electron transport chain of mitochondria [25] and on GABAergic pathways in the basal ganglia [32]. Apart from that, both oxidative stress and mitochondrial dysfunction have are also been attributed [27]. Functional neuroimaging in a few cases has shown that the striatonigral function appeared to be minimally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Since the phenomenology of Morbus Parkinson is not essentially different from the phenomenology of drug-induced parkinsonism, we assume that the UPDRS is able to measure AIP. In fact, several studies have utilized the UPDRS for the measurement of drug-induced parkinsonism [van Harten et al, 1996Lera and Zirulnik, 1999;Hassin-Baer et al, 2001;Jamora et al, 2007]. Additionally, the UPDRS is far more comprehensive and balanced than the often used Simpson-Angus Scale (SAS), which has been criticized for overemphasizing rigidity items (6 out 10 items measure rigidity, while only 1 item measures tremor) as well as other shortcomings recently highlighted by Loonen and van Praag [2007].…”
Section: Discussionmentioning
confidence: 99%
“…İlacı kullanan dört çocu-ğun ikisinde ilk 3 ayda ve diğer ikisinde de 2 yıl kronik kullanım sonucu serebellum atrofisi (psödoatrofi), tremor, ataksi ve minör EEG anomalileri görülmüştür (59). Özellikle ileri yaşta-ki hastalarda sodyum valproat kullanımı ile Parkinson hastalı-ğına benzer belirtiler görülmektedir (60,61). 36 hasta üzerinde yapılan bir prospektif çalışmada, 12 aydan uzun süreli sodyum valproat kullanımının geri-dönüşlü parkinsonizm ve kognitif zayıflamaya neden olduğu bildirilmiştir (62).…”
Section: Sodyum Valproatunclassified